2018
DOI: 10.1155/2018/2070895
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Spermatogenic Activity of Polyherbal Formulation in Oligospermic Males

Abstract: The therapeutic use of natural herbs is an ancient human civilization act and the numbers of people have reliance on their pharmacological properties and preferred to use the natural herbs. People also use to consume these herbs as supplements to energize, bolster, and eventually enhance sexual ability. Polyherbal formulation (PHF) is one of these herbal amalgams that can be used to treat sexual dysfunction including erectile dysfunction, impotence, ejaculation dysfunction, and hypogonadism. The pilot study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…This result agrees with the study of Adeoye et al (2021), who reported a similar significant decrease in sperm parameters, that is, in the count, motility, and even normal sperm in their study. The findings from semen parameters observed in this study also corroborate the study conducted by Hussain et al (2018), who demonstrated that a polyherbal formulation could produce a synergistic efficacy leading to an improvement in the major semen parameters in oligospermic males. The semen analysis results suggest that our herbal formulation of P. biglobosa aqueous seed extract improved semen parameters in the experimental animals at doses of 300 mg/kg Bwt; but it was cytotoxic at 500 mg/kg Bwt causing a decrease of semen parameters.…”
Section: Semen Analysissupporting
confidence: 90%
“…This result agrees with the study of Adeoye et al (2021), who reported a similar significant decrease in sperm parameters, that is, in the count, motility, and even normal sperm in their study. The findings from semen parameters observed in this study also corroborate the study conducted by Hussain et al (2018), who demonstrated that a polyherbal formulation could produce a synergistic efficacy leading to an improvement in the major semen parameters in oligospermic males. The semen analysis results suggest that our herbal formulation of P. biglobosa aqueous seed extract improved semen parameters in the experimental animals at doses of 300 mg/kg Bwt; but it was cytotoxic at 500 mg/kg Bwt causing a decrease of semen parameters.…”
Section: Semen Analysissupporting
confidence: 90%
“…A poly-herbal formulation (a combination of the roots of Chlorophytum borivilianum, seeds of Mimosa pudica, sap of Acacia Senegal, root of Astragalus membranaceus, seed coat of Plantago ovate, sap of Bombax ceiba, root of Eurycoma longifolia and rocky candy) was tested for its effect on the spermatogenic potential in oligospermic patients. After 90 days, there was a 256% increase in sperm concentration, a 154% increase in semen volume and a 215% increase in sperm motility, respectively (85).…”
Section: Phytotherapeuticamentioning
confidence: 96%
“…The polyherbal formulation (CFCT) was prepared by mixing the dried standardized extracts of the leaves of Costus speciosus, Fumeria indica, and Cichorium intybus in equal proportions. The dried extract of each of the drug and TQ (>98% purity) was reconstituted in a proportion of 1:1:1:0.1 to prepare a 100 mg/ml solution in a supersaturated solution of sugar (adapted from Hussain et al, 2018).…”
Section: Preparation Of Polyherbal Formulation (Cfct)mentioning
confidence: 99%
“…The dried extract of each of the drug and TQ (>98% purity) was reconstituted in a proportion of 1:1:1:0.1 to prepare a 100 mg/ml solution in a supersaturated solution of sugar (adapted fromHussain et al, 2018). The dried extract of each of the drug and TQ (>98% purity) was reconstituted in a proportion of 1:1:1:0.1 to prepare a 100 mg/ml solution in a supersaturated solution of sugar (adapted fromHussain et al, 2018).…”
mentioning
confidence: 99%